Predictors of successful whole-body hyperthermia in cancer patients: target temperature achievement and safety analysis - Hohneck, Anna; Schmitz-Solheid, Vivien; Gencer, Deniz; Schroeder, Maik; Rieß, Hartmut; Gerhards, Annette; Burkholder, Iris; Heckel-Reusser, Stefan; Gottfried, Julia; Hofheinz, Ralf-Dieter (Cancers, 2025)
Aim: This study aimed to investigate the effectiveness and safety of whole-body hyperthermia (WBH) in cancer patients, identifying predictive factors for successful treatment (reaching target temperature ≥ 38.5 °C) and assessing adverse effects. Methods: We conducted a retrospective analysis of 397 cancer patients receiving a total of 855 WBH treatment sessions at a single institution between January 2018 and December 2018. Results: A total of 855 WBH treatments were performed on 397 patients (76.6% female; median age 58 years). The most common cancer types included breast cancer (52.4%), followed by prostate cancer (13.1%) and gynecological cancers (10.6%), with 54.7% of patients having metastatic disease. Target temperature was reached in 90.1% (770 of 855) of sessions, with a median treatment time of 202 min and maximum temperature of 40.4 °C. Common side effects included headache (54.9%), skin reactions (11.7%), and cardiac effects (9.4%), with no serious adverse events. Serum creatinine (p = 0.01, OR 0.30, 95% CI: 0.11-0.78) and secale cornutum/galena co-medication during WBH (p < 0.001, OR 0.26 [0.12, 0.54]) emerged as independent predictors of achieving target temperature in multivariate analysis. Both elevated creatinine levels and the use of secale cornutum/galena were associated with an approximately 70% lower probability of achieving the target temperature. Conclusions: WBH demonstrates safety in cancer patients with high success rates in reaching target temperatures. Both elevated creatinine levels and the use of secale cornutum/galena were associated with a lower chance of reaching the target temperature and thus impacting and predicting WBH success.
Gesehen am 10.11.2025